2023
DOI: 10.1021/acs.jafc.3c00435
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Bitter Peptide Contributing to the Off-Flavor Attributes of Pea Protein Isolates

Abstract: The aversive bitter taste of pea protein ingredients limits product acceptability. Compounds contributing to the bitter perception of pea protein isolates were investigated. Off-line multi-dimensional sensory-guided preparative liquid chromatography fractionation of a 10% aqueous PPI solution revealed one main bitter compound that was identified by Fourier transform ion cyclotron resonance mass spectrometry and de novo tandem mass spectrometry (MS/MS) sequencing as the 37 amino acid peptide PA1b from pea album… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…Taylor et al (2004) identified a PA1b peptide variant in isolated pea protein that had insecticidal activity. More recently, Ongkowijoyo et al (2023) supported the presences of the bitter peptide PA1b in a commercial pea protein isolate. This bitter peptide was 37 amino acids in length.…”
Section: Non-volatile Organic Compoundsmentioning
confidence: 86%
See 3 more Smart Citations
“…Taylor et al (2004) identified a PA1b peptide variant in isolated pea protein that had insecticidal activity. More recently, Ongkowijoyo et al (2023) supported the presences of the bitter peptide PA1b in a commercial pea protein isolate. This bitter peptide was 37 amino acids in length.…”
Section: Non-volatile Organic Compoundsmentioning
confidence: 86%
“…However, they did find that the DoT for astringency was exceeded and thus at the concentration measured (1 mmol/kg) was sufficient to impart astringency but not bitterness. Ongkowijoyo et al (2023) also reported soyasaponin I concentration in a 10% solution of a commercial pea protein isolate was below the bitterness threshold and suggested that the bitterness observed was not due to this saponin. However, the conversion of DDMP saponins to soyasaponin I likely occurred during the production of the commercial pea protein isolates and resulted in a less bitter product due to the lower bitterness intensity of soyasaponin I compared to DDMP saponins (Heng, Vincken, Hoppe, van Koningsveld, Legger, et al, 2006;Heng, Vincken, Hoppe, van Koningsveld, Decroos, et al, 2006).…”
Section: Non-volatile Organic Compoundsmentioning
confidence: 98%
See 2 more Smart Citations
“…These proteins are known to sometimes contribute negative taste aspects such as astringency and bitterness (Glaser et al, 2020). There have been negative taste attributes associated with these proteins as well, for instance saponins (Heng et al, 2006) and a recently discovered bitter peptide in pea protein (Ongkowijoyo et al, 2023). Indeed, the challenges to recreate animal meat aroma and flavor with plant-based proteins are numerous.…”
Section: Principal Component Analysis and Hierarchical Cluster Analysismentioning
confidence: 99%